2020
DOI: 10.1111/exsy.12580
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for sentiment analysis on luxury hotel review

Abstract: This paper proposes a heuristic model for sentiment analysis on luxury hotel reviews to analyze and explore marketin g insights from attitudes and emotions expressed in reviews. We make several significant contributions to visual and multimedia analytics. This research will develop the practical application of visual and multimedia analytics as the research foundation is based on information analytics, geospatial analytics, statistical analytics and data management. Large amounts of data are generated by hotel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Blasi et al, 2020;Chen et al, 2021a), as well as user reviews and subsequent response strategies by management on related platforms (e.g. Chang et al, 2020;Jang & Moutinho, 2019;Schuckert et al, 2019), particularly in the hospitality industry.…”
Section: Netnographymentioning
confidence: 99%
“…Blasi et al, 2020;Chen et al, 2021a), as well as user reviews and subsequent response strategies by management on related platforms (e.g. Chang et al, 2020;Jang & Moutinho, 2019;Schuckert et al, 2019), particularly in the hospitality industry.…”
Section: Netnographymentioning
confidence: 99%
“…As the experience economy is becoming an industry-wide core component, luxury hotels as a part of the experience economy attempt to provide customers with a superior geographical location, 24-hour room service, an expansive space, expensive facilities, high-quality food, elegant aesthetics, privacy, security, and highly customized services [1,2]. With the popularity of luxury hotels in the hotel industry, exquisite decoration and upscale facilities have become the standard in every luxury hotel; therefore, customers have begun to pay attention to details and demand higher service and support facilities [3]. Thus, marketers and general managers of luxury hotels must attach great importance to the customer evaluations of service experiences provided by hotels and the subsequent behaviors via customers' perceptions of service experiential value regarding their stay in a luxury hotel.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, Almjawel et al [27] tried to conduct comprehensible sentiment analysis of online book reviews collected from Amazon to assist users in making efficient purchasing decisions. With respect to services, Chang et al [28] explored the service quality of the hotel from the standpoint of consumers. By analyzing the attitudes and emotions conveyed in customer comments, they found that professional services and clean rooms have a positive effect on improving customer satisfaction.…”
Section: A Sentiment Analysis In Business Domainmentioning
confidence: 99%